Morphological and Histological Study of Concha in Moorhen (Gallinula) - Khazaalwaad, Shaima (International Journal of Psychosocial Rehabilitation, 2020)
The present study reveals that the nasal cavity of moorhen formed of cranial and caudal conchae. The cranial one is the longest, extends just below the nares, and its base lies on the caudal of the nasal cavity. The caudal concha is shorter and smaller than the cranial one. Histologically Mucosa of (rostral and caudal) concha is lined by pseudo stratified ciliated columnar epithelium; there are large numbers of goblet cells. The lamina properia consists of connective tissue and rich with blood vessels, with secretory glands, the mucous glands lie at the beginning of properia, while the serous one situated in the termination of lamina properia. The cartilage lies below lamina properia and adventitia